How Women Are Treated During Facility-Based Childbirth in Four Countries: A Cross-Sectional Study With Labor Observations and Community-based Surveys. Issue 3 (September 2020) - Bohren, M.A.; Mehrtash, H.; Fawole, B.; Maung, T.M.; Balde, M.D.; Maya, E.; Thwin, S.S.; Aderoba, A.K.; Vogel, J.P.; Irinyenikan, T.A.; Adeyanju, A.O.; Mon, N.O.; et al.
Abstract : ( Lancet . 2019;394:1750–1763) While quality of obstetric care has been examined in low- and middle-income countries, including life-saving interventions and health outcomes, maternal experience is often left out of these evaluations. There is established evidence across the world of mistreatment during childbirth, including physical and verbal abuse, nonconsent for procedures performed, and discrimination. Previous studies on this mistreatment have varied widely in their methods, including location, timing and populations, presenting challenges in making cross-study comparisons. The current investigators aimed to develop tools for collecting data on the burden of mistreatment which can be compared across contexts. The study consisted of formative and measurement phases. The formative phase involved systematic reviews and qualitative research conducted in Nigeria, Ghana, Guinea, and Myanmar. Data from this phase informed the measurement phase, which included both continuous observations during labor and community-based postpartum surveys to measure the prevalence of mistreatment during childbirth in those countries. This article reported only on the measurement phase of the study.